The Implementation of Law Enforcement Against Criminal Acts of Mobbing Against Persons is Reviewed by Article 170 Paragraph (2) of the Criminal Code - Prihartono Prihartono; Muhammad Yusuf Siregar; Wahyu Simon Tampubolon; Risdalina Risdalina (Journal of Social Research, 2022)
Background: Indonesia is a country of law, the statement contained in the Explanation of the 1945 Constitution states that "The State of Indonesia is based on the law (rechtstaat) not based on mere power (machtstaat)". Objective: This study aims to find out and analyze the implementation of article 170 paragraph (2) 1 of the Criminal Code concerning criminal acts with joint energy committing violence against people. As well as knowing and analyzing the liability of criminal acts of mobbing in criminal law Methods: This research belongs to the normative type of research. So that it can be known that the liability of the criminal act of mobbing according to criminal law depends on the category of mobbing itself (Article 170 of the Criminal Code). Result: If the act is committed overtly and with concerted force using force against persons or goods is punished with imprisonment for not more than five years and six months, and if it results in injuries is subject to a maximum sentence of seven years. Burglary if violence results in serious injury are punishable by a maximum of nine years imprisonment. If violence results in death are subject to a maximum of twelve years. Conclusion: Based on the above explanation, it can be concluded that the liability of the criminal act of mobbing according to criminal law depends on the category of mobbing itself (Article 170 of the Criminal Code).